Cancer Stem Cells in Tumor Modeling: Challenges and Future Directions. Issue 11 (4th August 2021) - Dogan, Elvan; Kisim, Asli; Bati-Ayaz, Gizem; Kubicek, Gregory J.; Pesen-Okvur, Devrim; Miri, Amir K.
Abstract : Microfluidic tumors‐on‐chips models have revolutionized anticancer therapeutic research by creating an ideal microenvironment for cancer cells. The tumor microenvironment (TME) includes various cell types and cancer stem cells (CSCs), which are postulated to regulate the growth, invasion, and migratory behavior of tumor cells. In this review, the biological niches of the TME and cancer cell behavior focusing on the behavior of CSCs are summarized. Conventional cancer models such as 3D cultures and organoid models are reviewed. Opportunities for the incorporation of CSCs with tumors‐on‐chips are then discussed for creating tumor invasion models. Such models will represent a paradigm shift in the cancer community by allowing oncologists and clinicians to predict better which cancer patients will benefit from chemotherapy treatments. Abstract : Microfluidic tumors‐on‐chips have revolutionized anticancer therapeutic research by creating an ideal microenvironment for cancer cells. In this review, opportunities for the incorporation of cancer stem cells with tumors‐on‐chips are discussed for tumor invasion models. Such models represent a paradigm shift in the cancer community by allowing oncologists and clinicians to predict better which cancer patients can benefit from chemotherapy.